2009
DOI: 10.1016/j.jpeds.2009.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control in Youth with Diabetes: The SEARCH for Diabetes in Youth Study

Abstract: Objective To assess correlates of glycemic control in a diverse population of children and youth with diabetes. Study design This was a cross-sectional analysis of data from a 6-center US study of diabetes in youth, including 3947 individuals with type 1 diabetes (T1D) and 552 with type 2 diabetes (T2D), using hemoglobin A1c (HbA1c) levels to assess glycemic control. Results HbA1c levels reflecting poor glycemic control (HbA1c ≥ 9.5%) were found in 17% of youth with T1D and in 27% of those with T2D. Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
309
4
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 365 publications
(346 citation statements)
references
References 34 publications
25
309
4
8
Order By: Relevance
“…Previous research has suggested that African American and Hispanic youth are at risk for poor glycemic control while in pediatric care, although some studies have found that socioeconomic variables account for this effect. 7,17,18 Young adults from minority racial/ethnic backgrounds are considered at increased risk of poor transition outcomes. 19 Given our findings, this warrants further evaluation in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has suggested that African American and Hispanic youth are at risk for poor glycemic control while in pediatric care, although some studies have found that socioeconomic variables account for this effect. 7,17,18 Young adults from minority racial/ethnic backgrounds are considered at increased risk of poor transition outcomes. 19 Given our findings, this warrants further evaluation in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[4][5][6] Glycemic control, critical to long-term optimal outcomes for diabetes, has been shown to be poor for many youth as they age into adulthood. [7][8][9][10] Many agerelated factors could contribute to poor glycemic control, including changes in biological and psychosocial factors, and changes in access to care. 4,5 More specifically, the impact of age-related changes in diabetes care providers on glycemic control is not well understood.…”
mentioning
confidence: 99%
“…Socioeconomic status has been found to explain a large part of differences between children with and without migration background. 2,5,16 However, we adjusted for several environmental residence-based socioeconomic conditions without any change of our main finding. Ecological bias may be present with respect to ecological variables.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In Germany in particular, people with Turkish background, the largest ethnic minority, have been found to have poor health outcomes. [5][6][7] As possible reasons for lower acceptance of prevention and treatment offers, language barriers, lower socioeconomic status, another disease belief, or, on the other hand, factors within the healthcare system have been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Achievement of target glycaemia in the young adolescent group can be challenging with large studies reporting less than one-third achieving the recommended glycaemic targets [17] . The glycaemic control in the two clinical settings was assessed as part of an internal audit done at our centre.…”
Section: Hba1c and Glycaemic Controlmentioning
confidence: 99%